A simplified pre-conceptional laparoscopic cervical cerclage for cervical insufficiency: a retrospective study from a single center - Ledi Kuang; GuoLin Luo; Xin Tan; Hong Liao (BMC Pregnancy and Childbirth)
Abstract Background Cervical insufficiency is a pathological condition in obstetrics in which the cervix fails to retain the fetus before uterine contractions or labor (painless cervical dilatation). Patients usually have fetal loss in the mid-trimester or spontaneous pre-term birth due to painless cervical dilation. For non-pregnant women with cervical insufficiency, prophylactic laparoscopic abdominal cerclage (LAC) has been reported to improve pregnancy outcomes, such as live birth, neonatal survival, and full-term delivery rate. Conventional LAC involves opening the vesicular space and separating the anterior broad ligament leaves. In our surgical procedure, these two steps were omitted. Methods An observational study was conducted retrospectively on patients who underwent a simplified pre-conceptional LAC between January 2015 and December 2022 at West China Second University Hospital, Sichuan University. Follow-ups for all the patients ended at the delivery of the fetus. Subsequently, clinical characteristics, perioperative data, and obstetric outcomes were recorded and analyzed. Results In total, 108 patients were included in a pre-conception LAC group Mean operation time was 56.8 ± 22.8 min, and mean estimated blood loss was 21.4 ± 23.6 mL. Only one case of urinary retention was classified as a grade I postoperative complication, according to the Clavien–Dindo classification. No severe complications or sequelae were observed during the perioperative period. Obstetric outcomes from 98 patients were collected: three patients had miscarriages, and 95 had live births. Of the 95 live births, 4 were twins and 91 were singletons. Two patients had vaginal delivery, and 93 underwent Cesarean section; mean neonatal weight was 3310.2 ± 382.1 g. Conclusion A simplified pre-conceptional LAC is a simple, safe, and effective method for women with cervical insufficiency. Thus, it is worthy of promotion to assist women with cervical insufficiency in achieving improved obstetric outcomes. Vaginal delivery after LAC is possible once the tape is removed before labor.